2013
DOI: 10.1039/c3cp53333f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zn2+ and Pb2+ dopants on the activity of Ga2O3-based photocatalysts for water splitting

Abstract: leading to an enhanced photocatalytic activity for water splitting. Unlike Zn 2+ ions, Pb 2+ ions are coordinated by oxygen atoms to form polyhedra as dopants, resulting in distorted surface structure and fast decay of photogenerated electrons of b-Ga 2 O 3 . These results suggest that the Pb dopants act as charge recombination centers expediting the recombination of photogenerated electrons and holes, thus decreasing the photocatalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 57 publications
2
87
0
Order By: Relevance
“…This can be explained by the situation that only the b phase is exposed on the surface of Ga 2 O 3 sample calcined at 903 K with the a/b core/shell structure and the a-b phase junction doesn't work. The results suggest that the presence of the a-b phase junction and the exposure of both phases on the surface are essential for the enhancement of photocatalytic activity, which is also demonstrated by our recent study on the ZnGa 2 O 4 -b-Ga 2 O 3 heterojunction [116]. The analysis of band structure indicates that the a-b phase junction exhibits type-II band alignment, which is favorable for charge separation.…”
Section: Uv Raman Spectroscopic Study On the Phase Transformation Of mentioning
confidence: 57%
“…This can be explained by the situation that only the b phase is exposed on the surface of Ga 2 O 3 sample calcined at 903 K with the a/b core/shell structure and the a-b phase junction doesn't work. The results suggest that the presence of the a-b phase junction and the exposure of both phases on the surface are essential for the enhancement of photocatalytic activity, which is also demonstrated by our recent study on the ZnGa 2 O 4 -b-Ga 2 O 3 heterojunction [116]. The analysis of band structure indicates that the a-b phase junction exhibits type-II band alignment, which is favorable for charge separation.…”
Section: Uv Raman Spectroscopic Study On the Phase Transformation Of mentioning
confidence: 57%
“…4 shows the D band and G band of GO in different samples. Of particular note are the position of the G band and the intensity of I D /I G [20] and [21]. The position of the G band shows the reduction degree of GO, and it can be seen in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…It has also been reported that Ga 2 O 3 -based photocatalyst has a high efficiency for water splitting. 13 With band gap being narrowed to the visible light region in N-alloyed Ga 2 O 3 , a larger spectral range of the sunlight can be utilized in photocatalyst application. Figure 4 shows the θ-2θ XRD patterns of the films with nitridation treatment at different temperatures.…”
mentioning
confidence: 99%
“…It has been demonstrated that Ga 2 O 3 is a promising candidate for solar blind UV photodetector, power devices, and photocatalysis in solar water splitting. [10][11][12][13] As a versatile functional material, Ga 2 O 3 not only has the various device applications by utilizing its intrinsic properties, but also owns the flexibility to form important material systems by alloying with other materials, which have been playing a crucial role in different kinds of device applications. As shown in Fig.…”
mentioning
confidence: 99%